Modelagem de distribuição de espécies comerciais da flora ameaçadas no estado do Pará: um enfoque sobre as unidades de conservação - GOMES, Vitor Hugo Freitas (Universidade Federal do Pará, 2018)
In order to identify potential sites for endangered species conservation were compared distribution models of commercial endangered species of the states of Pará flora, with maps of protected areas in the state, and observe the occurrence of these species within and outside these areas. This study aims to compare distribution models of endangered commercial species of the state of Pará flora, with the maps of protected areas in the state, and observe the occurrence of these species within and outside these areas. Through this comparison objective is to indicate potential sites for conservation of these species. Currently 53 species of the state of Pará flora are threatened with extinction. The species chosen are part of the Conservation Project pau-cravo, castanheira, pau-rosa and and maçaranduba, developed through a partnership between Goeldi Museum (MPEG), Ominia Minerals / Alcoa and Foundation of Research and Development (FADESP). The development of these models was made by the software Maxent 3.3.3, which uses the method of maximum entropy to analyze the data of species occurrence and generate their distribution models. The distribution models show which areas are suitable for the presence of the species, based on data of occurrence, and the characteristics of these sites, composed by environmental variables.